2010
DOI: 10.1111/j.1365-2893.2009.01240.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of chronic viral hepatitis in people of south Asian ethnicity living in England: the prevalence cannot necessarily be predicted from the prevalence in the country of origin

Abstract: The prevalence of hepatitis B and hepatitis C in immigrant communities is unknown. Immigrants from south Asia are common in England and elsewhere, and the burden of viral hepatitis in these communities is unknown. We aimed to determine the prevalence of viral hepatitis in immigrants from south Asia living in England, and we therefore undertook a community-based testing project in such people at five sites in England. A total of 4998 people attending community centres were screened for viral hepatitis using ora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
86
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(93 citation statements)
references
References 19 publications
5
86
2
Order By: Relevance
“…10 A 2013 UK study demonstrated that 1.1% of tested individuals were positive for HBsAg; 11 in 2009, the prevalence of HBV among migrants in the UK was estimated to be 4%, 12 ranging from 0.1% to 17.4% depending on ethnic group and study method. [13][14][15][16][17][18] In 2012, the National Institute for Health and Care Excellence (NICE) recommended that all people born in a country with HBV prevalence of ≥2% should be offered a HBV test and that testing is offered in primary care. 19 In 2011, approximately 7.5 million (13%) individuals living in England and Wales were born outside of the UK.…”
Section: Introductionmentioning
confidence: 99%
“…10 A 2013 UK study demonstrated that 1.1% of tested individuals were positive for HBsAg; 11 in 2009, the prevalence of HBV among migrants in the UK was estimated to be 4%, 12 ranging from 0.1% to 17.4% depending on ethnic group and study method. [13][14][15][16][17][18] In 2012, the National Institute for Health and Care Excellence (NICE) recommended that all people born in a country with HBV prevalence of ≥2% should be offered a HBV test and that testing is offered in primary care. 19 In 2011, approximately 7.5 million (13%) individuals living in England and Wales were born outside of the UK.…”
Section: Introductionmentioning
confidence: 99%
“…The 67 studies identified were done in the USA (n = 27), Europe (n = 27; mostly France and the United Kingdom [UK]), Asia (n = 4), Australia (n = 4), South America (n = 3), Egypt (n = 1) and Saudi Arabia (n = 1). We identified 24 nonintegrated and 41 integrated studies, plus two studies that used both strategies (the latter are shown in the paragraph below for the results of the nonintegrated part of their program, and in the subsequent paragraphs for the results of the integrated part of their program) [46,47]. A total of 85% (22/26) of the nonintegrated programs and all of the integrated programs were from low HCV-prevalence countries.…”
Section: Resultsmentioning
confidence: 99%
“…A program targeted at firefighters [49] used home specimen collection kits for serum collection. A program targeted at migrants [46] initially used oral fluid HCV antibody tests followed by a blood test for those who tested positive (no further details reported). In the majority (16/22) of the programs, participants were also screened for other infections (mostly HIV and hepatitis B virus …”
Section: Resultsmentioning
confidence: 99%
“…Prevalence rates vary by region and have changed over time, so the rate of infection in immigrants is difficult to estimate from the country of origin alone. 22 Only 300 of the 7,700 new cases of chronic HBV diagnosed each year acquire the infection in the UK, the rest acquiring the chronic infection overseas. 7 …”
Section: Routes Of Infectionmentioning
confidence: 99%